Phenomenology of Adult Education as an Interdisciplinary Field: Revisiting Sherman Stanage - Jeff Zacharakis (Adult Education Research Conference, 2014)
The purpose of this paper’s theoretical analysis is to reintroduce and explore Stanage’s phenomenological analysis of adult education, and offers insight to how this field of study can expand its intellectual boundaries to become an interdisciplinary force of learning that permeates all other academic disciplines.